Developing a drink from sweet almond (Prunus dulcis) - Salvá Ruiza, Bettit (2017)
A drink was developed from sweet almonds (Prunus dulcis) using 3 factors at different levels: almond: water ratio (1: 3, 1: 4, 1: 5); percentage of soluble solids (7 and 10º Brix) and sterilization time (15 and 25 minutes). The beverages were subjected to a sensory analysis where the color, odor, taste and consistency were evaluated, for which a completely randomized block design (DBCA) with 50 untrained panelists was used; using a verbal hedonic scale with 7 points.The data was processed in the Statgraphics Centurión plus v.16 software. In this way, the optimized formula was determined (almond dilution: water of 1: 5, percentage of soluble solids of 10 ° Brix and a sterilization time of 25min at 121 ° C), which obtained a higher level of liking (average of 5.6 out of 7).To this treatment, the physicochemical, proximal chemical analysis, mineral analysis, and finally the commercial sterility analysis were carried out, guaranteeing that an innocuous beverage was obtained. Finally, a preference test was carried out for ordering with almond drinks from two commercial brands and with the formula optimized, observing that it presents a greater preference in terms of flavor, color and consistency.